Environmental surveillance of Legionella pneumophila in hot water systems of hotels in Morocco - Abdelwahid Assaidi (IWA Publishing, 2021)
Objective: Environmental monitoring of Legionella in hot water systems of hotels in Morocco was performed during the period from January 2016 to April 2018. A total of 149 water samples from 118 different hotels were analyzed. Methods: A total of 149 water samples from 118 different hotels were analyzed. Possible risk factors were prospectively recorded, and data were analyzed in connection with building and plumbing systems characteristics. Data about building and risk factors were collected through a questionnaire survey. Results: Out of the 149 samples, 77(51.7%) were positive for L. pneumophila. Serological typing of the isolates revealed that 54 (70.1%) are L. pneumophila serogroup 2–15 and 23 (29.9%) are L. pneumophila serogroup 1. 56.8% of all buildings were colonized by L. pneumophila. Counts were over 1,000 CFU/L in 44%. Contamination was strongly correlated with temperature in the circulation, the age of the premise plumbing and the size of the building. Conclusions: The results showed a relevant exposure to L. pneumophila in the community and the identified risk factors can serve as indicators for risk assessment and relevant actions. HIGHLIGHTS Travel and stays in accommodation sites will continue to represent a significant cause of travel-associated LD, especially in a region of increasing travel to countries that may not have the expertise or resources to prevent or reduce the risk of exposure to Legionella species.; Legionella in Moroccan hotels is a major concern still poorly investigated.; Legionella found in 51.7% of analyzed samples and 56.8% of investigated buildings.; Temperature in the circulation, age of the premise plumbing, and the size of building were positively associated with contamination.; The results showed a relevant exposure to L. pneumophila in the community and the identified risk factors can serve as indicators for risk assessment and relevant actions.;